2016
DOI: 10.1002/mnfr.201500966
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tissue, diet, and enzymatic remodeling on cardiolipin fatty acyl profile

Abstract: Cardiolipin is a specialized phospholipid found primarily in the inner mitochondrial membrane. Because of its unique dimeric structure, cardiolipin plays an important role in mitochondrial function, stability, and membrane fluidity. As such, cardiolipin is subject to a high degree of remodeling by phospholipases, acyltransferases, and transacylases that create a fatty acyl profile that tends to be highly tissue-specific. Despite this overarching regulation, the molecular species of cardiolipin produced are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 152 publications
(282 reference statements)
1
40
0
Order By: Relevance
“…Interestingly, it has been shown that cardiolipin anchors cytochrome c to the inner mitochondrial membrane and that externalization of cardiolipin (e.g. due to peroxidation) to the outer mitochondrial membrane releases cytochrome c in the cytoplasmic space (Bradley et al, 2016;Chu et al, 2013). Thus, it is possible that the rapid modifications in mitochondrial capacities and the increased cytochrome c effect observed in our study at day 1 might be related to modifications of mitochondrial cardiolipin.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, it has been shown that cardiolipin anchors cytochrome c to the inner mitochondrial membrane and that externalization of cardiolipin (e.g. due to peroxidation) to the outer mitochondrial membrane releases cytochrome c in the cytoplasmic space (Bradley et al, 2016;Chu et al, 2013). Thus, it is possible that the rapid modifications in mitochondrial capacities and the increased cytochrome c effect observed in our study at day 1 might be related to modifications of mitochondrial cardiolipin.…”
Section: Discussionmentioning
confidence: 64%
“…Two different mechanisms are believed to be used by the cell to ensure mitochondrial homeostasis and survival; apoptosis and mitophagy but, to the best of our knowledge, none of these has been considered in the context of thermal acclimation. Of interest, both processes are potently regulated by cardiolipin and its function to anchor cytochrome c to the inner mitochondrial membrane, and have been shown to be triggered by cardiolipin modifications (Bradley et al, 2016;Chu et al, 2013;Sorice et al, 2004). The release of cytochrome c triggers apoptosis and cell death (Goldstein et al, 2000), and it is therefore possible that the increased cytochrome c effect we observed upon warming induced this mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…These lipids are subjected to a high specificity in fatty acyl remodeling, depending on the cell type, with LA being the predominant lipid of this type. In mammalian mitochondria, the fatty acyl composition of cardiopilins can be influenced by lipids in the environment, e.g., the organism's diet, and any alterations in cardiolipin composition have pathological consequences (81). In the presence of excess OA, LA may be replaced by OA during cardiolipin synthesis in mitochondria, resulting in the abnormal morphological features of these organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Another remarkable observation is the length of the acyl chains of the identified PGs. The CL acyl chain length varies in composition in various organs, 37 but in general the most abundant species is linoleic acid (18:2) followed by oleic acid (18:1). The length of fatty acyl chains and their degree of (un)saturation define the exact function of a phospholipid, and alterations have been associated with disease.…”
Section: Discussionmentioning
confidence: 99%